If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(8y + 3) = 0 Reorder the terms: -6(3 + 8y) = 0 (3 * -6 + 8y * -6) = 0 (-18 + -48y) = 0 Solving -18 + -48y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -48y = 0 + 18 Combine like terms: -18 + 18 = 0 0 + -48y = 0 + 18 -48y = 0 + 18 Combine like terms: 0 + 18 = 18 -48y = 18 Divide each side by '-48'. y = -0.375 Simplifying y = -0.375
| 2=4(-x+3)+8x | | 9=k(3/2) | | 9-10=-4/3 | | 4x^2-10x=2 | | -2x=1/2 | | 3(-4+8m)+5= | | X^2=1/144 | | -8(1/4)(6) | | -5n+9=n+3 | | 4x+5=-5x-11 | | -8(z-973)=656 | | 4x=-1/4 | | -2.35x+6.75=-2.28 | | 9x/-11-7-5 | | -8(7w-6)-9w= | | y=-3(-6)-7 | | 2x-15=8x+5 | | 7m-2=33 | | -7(2-5x)= | | -27=r/12-18 | | -2(v+3)+3v= | | 65=12x+5 | | 5x^2-34x+68=0 | | -12+7(d-1)+14-d=p | | 4x+7=3(x+2)+(x+2)5 | | X+2=-x-10 | | 2(-7+9k)= | | 3m+3z=23 | | 5w-2(3x-5w)-5x= | | a=1.9044+1.23(3) | | 4x/-710 | | 7c+2c+8c-3= |